CURRICULUM DEVELOPMENT STRATEGIC MANAGEMENT MODEL ISLAMIC INTERNATIONAL BOARDING SCHOOL (IIBS) IN THURSINA IIBS MALANG - Dwi Fitri Wiyono (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2021)
The aims of this study to find the process of formulating, implementation and evaluation of the curriculum strategy strategy for the International Islamic Boarding School Islamic education model at the Thursina IIBS Islamic Education Institute Malang Regency. The method in this study uses a qualitative approach, case study research with multi-site design, data collection techniques, namely: interviews, observations, and document studies, analysis techniques using single cases and cross-cases. The results of this study are: (1) Formulation of the curriculum development strategy of the International Islamic Boarding School model through the following stages: first, the input strategy: combining the Islamic boarding school curriculum, the national curriculum and the international curriculum namely the Coumbridge Curriculum, graduates from the International Islamic Boarding School (IIBS) will have a charter Coumbbrige, Second, process strategy: developing curriculum through language strengthening and self-development with global insight (enrichment and extension), third, output strategy: commitment to the quality of graduates who have an Islamic personality (morally excelent), globally minded (internationally minded) , and spirited leader (an inspiring leader). (2) Implementation of the strategy of developing Islamic education curriculum model International Islamic Boarding School (IIBS), implementation of the curriculum through the process of organizational culture and refocusing the organization and specialization class (Moslem scholar, entrepreneur, sciencepreneur, professional) (3) Evaluation of strategy development of Islamic education curriculum the International Islamic Boarding School model, the evaluation adapts to the standard curriculum blending the pesantren curriculum, national, and international, the evaluation is carried out holistically starting from the input, process, output, and outcome by involving all stakeholders in curriculum development.